Assurances to Prevent Violation of Citizenship Rights of Defendant on Probation based on Imam Khomeini’s Views - Ebrahim Yaghouti; Shiva Azizan Azizan (پژوهش‌نامه متین, 2021)
Criminal procedure comprises of various stages, one of which is putting the defendant on probation. By virtue of statute laws, the defendant on probation shall enjoy certain rights including rights for the duration of the term of probation, the right to exercise his rights, right to inform his relatives, right to enjoy medical examination, right to select an attorney, and the right to arraign. Violation of each one of these rights may result in enforcing criminal, civil and disciplinary sanctions per occasion. This paper is about determining citizenship rights of the defendant on probation and sanctions against violating those rights based on Imam Khomeini’s views. The methodology of this paper is descriptive-analytical in type. Findings of the paper suggest that many works by Imam Khomeini contain various rules on grounds and dimensions of the nation’s rights. Imam Khomeini has presented imperative and positive rules on some citizenship rights of the defendants on probation such as the right to select an attorney in particular, and other citizenship rights at this stage of adjudication in general. .